Displaying consideration via EHM ('uhm') in Hebrew WhatsApp dialogues. (June 2021) - Marmorstein, Michal
Abstract: Vocalizations, specifically of the nasal type (abbreviated EHM), are commonly used in Hebrew WhatsApp dialogues. Originating in oral conversation, in which they serve as facilitators or indicators of thinking and planning, vocalizations undergo repurposing in WhatsApp and are deployed as markers of consideration in socially charged or implicative contexts. The core function of EHM as a displayer of consideration is variously particularized in different sequential positions. In launching a sequence, EHM is used to attenuate a request or preface an appeal for collaborative consideration. In response position, EHM can preface either an aligning or a non-aligning response, as well as implement an action delay. In either case, EHM indicates that a straightforward (type-conforming) response cannot be given and that the matter at issue and the persons involved require consideration. In follow-up position, EHM marks the extended consideration needed to digest a non-favored response. In sequence expansions, EHM indicates that further thought has been invested in order to come up with a better response. The relational work accomplished by EHM in messaging clearly diverges from the stereotypical and often ironic use of vocalizations in monologic writing. This evidences the high adaptability of vocalizations, as contextual indices, to the form of communication in which they are used.